Pelatihan Dasar Kepemimpinan (Leadership) Pada Anggota OSIS SMK Satrya Budi 2 Perdagangan Kab. Simalungun - Rizki Alfadillah Nasution; Ilham Syahputra Saragih; Rizky Khairunnisa Sormin (LPPM STIKOM Tunas Bangsa, 2021)
Leadership in an organization's is an important factor in an organization's success toward a set goal. To answer and solve the various problems that occur in organizational leadership in vocational high school (SMK) Satrya Budi 2 Perdagangan requires specifically a training program. This,training useful provides a comprehensive and in-depth understanding of the fundamentals of leadership. Student council leaders are required to learn to understand the basics of leadership so that later in the day leading their members can have a disciplined and responsible attitude in achieving organizational goals. In addition, this program is implemented to form shaping personality character and hone soft skills that which will be useful to them after graduate and entering the workforce. The results of this devotional activity are expected to provide a comprehensive picture of the basics of leadership. And with this leadership training is expected to be able to base or underlying students, especially student council members, about/by understanding the leadership knowledge and fostering the spirit of leadership on him in the future.